Manajemen Pembelajaran Program P5PPRA di Madrasah Ibtidaiyah - Sofya, Ayu; Novita, Nursyahbani Chusnul; Wigati, Indah (Limas PGMI, 2025)
The Pancasila and Rahmatan Lil Alamin (P5PPRA) student profile strengthening program with the theme "Bhinneka Tunggal Ika" is designed to integrate Pancasila values and the principle of diversity in learning activities that are relevant to students' daily lives. This study uses a qualitative approach with a descriptive method, then observation, interviews and documentation as data collection techniques. The results of the study show that the implementation of P5PPRA in MIN 2 Palembang City has been carried out through systematic planning, which includes the preparation of a thematic curriculum, teacher training, and continuous evaluation. The theme "Bhineka Tunggal Ika" is implemented through project-based learning, group discussions and collaborative activities to encourage students to understand the importance of diversity and unity.